Diagnostic Accuracy of Contrast Enhanced Computed Tomography in Detecting Bronchogenic Carcinoma-Experience At Liaquat National Hospital - Nazish Khaliq; Ameet Jesrani; Muhammad Ayub Mansoor; Waseem Mehmood Nizamani; Roomi Mahmud; Mustansir H Zaidi (Journal of the Dow University of Health Sciences, 2017)
Background: Lung cancer is one of the most common malignancies worldwide. Cigarette smoking is considered as the major risk factor for bronchogenic carcinoma. The four common types namely – squamous cell; small cell; adeno and large cell carcinomas account for more than 90% cases of Bronchogenic carcinoma. Initially it is detected by plain chest radiography but it is considered as an insensitive. Computed Tomography can detect early stage disease 6-10 times more frequently than X-rays. Objective: To determine diagnostic accuracy of Contrast Enhanced Computed Tomography in detecting Bronchogenic Carcinoma taking histopathology as Gold Standard. Methods: Total 157 patients presented with pulmonary nodule or suspicious lesion on X-Ray and had history of haemoptysis, weight loss, cough and chest pain for more than two months were included. CT was performed with I/V contrast. Axial images were taken with patients lying supine. Images were analyzed. The same radiologist assessed the patient included in the study. All patients then underwent biopsy and samples were sent for histopathology. Sensitivity, specificity, and accuracy of computed tomography were calculated using histopathology as gold standard. Results: There were 101 male and 56 female patients. The mean age was 59.77±7.97 years. On CT Scan 89 patients were diagnosed with bronchogenic carcinoma. On histopathology, 90 patients were diagnosed with bronchogenic carcinoma. The sensitivity of CT Scan was 90.0%, specificity was 88.0% and diagnostic accuracy was 89.1%. Conclusion: CT scan is a sensitive imaging modality in diagnosing malignancy in pulmonary lesions.